2018
DOI: 10.1021/acsami.7b19721
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrically Curved Hyperbolic Metamaterial Structure with Gradient Thicknesses for Enhanced Directional Spontaneous Emission

Abstract: We demonstrate hyperbolic metamaterials (HMMs) on a curved surface for an efficient outcoupling of nonradiative modes, which lead to an enhanced spontaneous emission. Those high-wavevector plasmonic modes can propagate along the curved structure and emit into the far field, realizing a directional light emission with maximal fluorescent intensity. Detailed simulations disclose a high Purcell factor and a spatial power distribution in the curved HMM, which agrees with the experimental result. Our work presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The study suggested that the Purcell factor increases as the unit cell thickness decreases, exhibiting the maximum enhancement factor of about 40. Related analysis was done in work 84 , where the number of layers and their thickness were varied to study changes of the Purcell factor. The HMM was composed of alternate silver and silicon layers with a dipolar emitter on top of it.…”
Section: Metal-dielectric Multilayersmentioning
confidence: 99%
“…The study suggested that the Purcell factor increases as the unit cell thickness decreases, exhibiting the maximum enhancement factor of about 40. Related analysis was done in work 84 , where the number of layers and their thickness were varied to study changes of the Purcell factor. The HMM was composed of alternate silver and silicon layers with a dipolar emitter on top of it.…”
Section: Metal-dielectric Multilayersmentioning
confidence: 99%
“…However, due to the limitation of dissipation and large impedance mismatch in bulk HMMs, it has been demonstrated theoretically and experimentally that the emission rate and intensity will be higher within the HMMs than near the interface. For example, using nanopatterned Ag–Si multilayer HMMs, the spontaneous recombination rate in InGaN/GaN quantum wells (QWs) can be enhanced to ≈160‐fold in broadband .…”
Section: D Bulk Hyperbolic Metamaterialsmentioning
confidence: 99%
“…Compared with other optical metamaterials, like chiral and split ring resonator–based metamaterials, HMMs have advantages of relative ease of fabrication at optical frequencies, broadband nonresonant and 3D bulk responses, and flexible wavelength tunability. As a result, HMMs have attracted widespread interest and become a good multifunctional platform for many exotic applications, such as optical negative refraction and light beam steering, subdiffraction‐limited imaging and nanolithography, spontaneous and thermal emission engineering, ultrasensitive optical, biological, and chemical sensing, omnidirectional and broadband optical absorption …”
Section: Introductionmentioning
confidence: 99%
“…Selective coupling between 3D WGMs in rolled-up microtubes and localized surface plasmon resonances (LSPRs) has been demonstrated recently. ,, Utilizing the naturally existing outer notch (i.e., the end point of nanomembranes after rolling), a localized hotspot can be created at the sub-100 nm gap by deposition of a thin metal layer, which renders the design promising for ultrasensitive and spatially selective detection of analyte binding events. Apart from integrating dielectric tubes with metal nanostructures, direct rolling of stacked dielectric and metal layers have also been investigated with other exotic optical properties, such as anisotropic metamaterials with hyperbolic dispersion. , Theoretical work on rolled-up metamaterial-based biosensors has been reported with an improved sensing performance compared with conventional all-dielectric rolled-up microtubes …”
Section: Rolled-up Nanomembranes As Microtubular Sensorsmentioning
confidence: 99%
“…Apart from integrating dielectric tubes with metal nanostructures, direct rolling of stacked dielectric and metal layers have also been investigated with other exotic optical properties, such as anisotropic metamaterials with hyperbolic dispersion. 132,133 Theoretical work on rolled-up metamaterial-based biosensors has been reported with an improved sensing performance compared with conventional all-dielectric rolled-up microtubes. 134 Rolled-Up Microtube-Based Passive Optical Sensors.…”
Section: Acs Sensorsmentioning
confidence: 99%